Optimum Portfolio Analysis of Black-Litterman Model in The Indonesian Stock Exchange on Consumer Goods Industrial Sector - Meilina Pudjiani; Yusman Syaukat; Tony Irawan (Bina Nusantara University, 2020)
The aim of the research was to identify the allocation of optimum portfolio formation in consumer goods sector at Indonesian Stock Exchange from 2014 to 2018 by using Black-Litterman model. This quantitative research used secondary data on stock prices of the consumer goods sector on the Indonesian Stock Exchange from January 2014 to December 2018 which was obtained from Yahoo Finance and the Indonesia Stock Exchange. Four stocks formed the optimum portfolio of consumer goods sector identified by using Black-Litterman model. Those are stocks of PT Indofood CBP Sukses Makmur Tbk, PT Kimia Farma Tbk, PT Indofarma Tbk, PT Indofarma Tbk, and PT HM Sampoerna Tbk. The results show that stock with the biggest proportion was ICBP’s with proportion of 68,5379%. Meanwhile the smallest proportion was INAF’s, which is 3,0277%. The mean return was calculated from this proportion, resulting in 3,678% while the risk value was 1,471%.